Modus Operandi Tindak Pidana Perdagangan Orang Yang Berkedok Asisten Rumah Tangga - Salamena, Fredza Glen; Toule, Elsa Rina Maya; Ubwarin, Erwin (Faculty of Law Pattimura University, 2023)
Introduction: Trafficking in persons is a form of ill-treatment of human beings that violates the dignity and worth. The crime of trafficking in persons is inseparable from the various methods used by the perpetrators, these methods are usually called the modus operandi. The mode that is run is usually carried out individually or in groups. The strategies used by trafficking syndicates in carrying out their modus operandi are very organized, so they can easily persuade and recruit victims. This not only deprives the victim of human rights but also makes the victim vulnerable to abuse, forced labor, psychological trauma and death. Purposes of the Research: This writing aims to determine the modus operandi and efforts to handle the criminal act of trafficking in persons under the guise of a household assistant.Methods of the Research: The research method used in this paper is Juridical Empirical. Research location The place where the research material was taken is the Ambon District Court. Population, Sample, and Respondents. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as legal materials collection techniques, then processing techniques use the editing, data classification, and data analysis stages.Results of the Research: The results of this study indicate that the success of trafficking in persons is due to the modus operandi carried out by the perpetrators so organized that trafficking in persons is successfully carried out. Thus the need for efforts to handle the crime of trafficking in persons. Penal and non-penal handling efforts are carried out: penal efforts are carried out based on legal regulations that are centered on the applicable laws and regulations. Meanwhile, non-penal efforts are the prevention process before the occurrence of the criminal act of trafficking in persons, including social education, socialization to the community, and patrol activities as a form of supervision.